The Impact of National Security Laws on Religious and Ethnic Minorities in Indonesia (Indonesian Minority Justice Review, 2024)
This paper critically examines the impact of Indonesia's national security laws on religious and ethnic minorities, assessing how such laws might be used to justify discrimination, persecution, or exclusion. While Indonesia’s national security laws, including the 2002 Anti-Terrorism Law and the 2013 National Security Bill, are intended to protect the state against threats, they have had unintended consequences for minority communities, particularly in terms of surveillance, restrictions on religious practices, and suppression of cultural expression. The study analyzes legal texts, government reports, and case studies of minority groups—such as the Ahmadiyya Muslim community and indigenous peoples—who have been disproportionately affected by national security measures. Through interviews with legal experts and human rights advocates, the paper explores the ways in which security laws are sometimes wielded as tools of state control, exacerbating tensions between majority and minority groups. The findings suggest that national security laws often fail to consider the human rights implications for minorities, leading to increased vulnerability and marginalization. The paper concludes by recommending reforms to national security laws that include stronger protections for minority rights, greater judicial oversight, and safeguards to prevent discrimination under the guise of national security.